Activism and Rhetoric : Theories and Contexts for Political Engagement - Lee, JongHwa; Kahn, Seth (New York, NY : Routledge, 2020)
The second edition of this formative collection offers analysis of the work rhetoric plays in the principles and practices of today's culture of democratic activism. Editors JongHwa Lee and Seth Kahn--and their diverse contributors working in communication and composition studies both within and outside academia--provide explicit articulation of how activist rhetoric differs from the kinds of deliberative models that rhetoric has exalted for centuries, contextualized through and by contributors' everyday lives, work, and interests. New to this edition are attention to Black Lives Matter, the transgender community, social media environments, globalization, and environmental activism. Simultaneously challenging and accessible, Activism and Rhetoric: Theories and Contexts for Political Engagement is a must-read for students and scholars who are interested in or actively engaged in rhetoric, composition, political communication, and social justice.
Works Cited8 Memory War: Activist Rhetoric for Historical Justice; History: Japanese Military Sexual Slavery (aka, "Comfort Women"); Reflection: How I Became Involved in the Movement; The NYT Article: The Agreement and the Statue; Memory War: The Final (Re)Solution and Activist Rhetoric for Historical Justice; Works Cited; Part III Modalities and Audiences; 9 Raging Media: Investing in an Infrastructure for Resistance; Spawn of the Raging Chicken; Hollowing Out Democracy; Investing for the Long-Haul; Notes; Works Cited
10 A Conservative Professorial Pundit in Liberal Surroundings: An Uneven Odyssey Projected through 2020
OCLC-licensed vendor bibliographic record.
Keywords: Political participation; Communication in politics; Rhetoric -- Political aspects; Communication -- Political aspects; LANGUAGE ARTS & DISCIPLINES / Communication; LANGUAGE ARTS & DISCIPLINES / Rhetoric